The Soviet Merchant Marine of the 1990s: Still a Competitive Threat? - Laura B. Forker (Journal of the Transportation Research Forum, 1991)
The Soviet Merchant Marine has been commonly portrayed as a competitive threat to Western shipping, due to its rapid expansion in the 1960s and early 1970s. What has been the pattern of growth of the Soviet merchant fleet in recent years? Is the Soviet merchant marine a potential disrupter of Western shipping equilibrium? These concerns are addressed by examining the structure and economics of Soviet shipping, the fleet's size over the past decade, and the Soviets' participation in international freight transport.
Keywords: 330; Merchant Marine; Transportation